2022
DOI: 10.1155/2022/1688826
|View full text |Cite
|
Sign up to set email alerts
|

Lignans from Mosla scabra Ameliorated Influenza A Virus-Induced Pneumonia via Inhibiting Macrophage Activation

Abstract: The lower respiratory tract infection, induced by influenza virus, coronaviruses, and respiratory syncytial virus, remains a serious threat to human health that can cause a global pandemic. Thus, finding effective chemicals and therapeutic measures to advance the functional restoration of the respiratory tract after infection has been the emphasis of the studies on the subjects. Mosla scabra is a natural medicinal plant used for treating various lung and gastrointestinal diseases, including viral infection, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 57 publications
(70 reference statements)
0
3
0
Order By: Relevance
“…MAPK and autophagy signaling pathways contributed to IAV virus-induced inflammation and lung injury [ 65 , 66 ]. FOXO signaling pathway has also been showed playing an important role in the IAV-induced alveolar macrophage dysfunction [ 67 ], and FoxO1 negatively regulated cellular antiviral response by promoting degradation of IRF3 [ 68 ]. The mTOR signaling pathway was most important for early IAV replication, and the use of mTOR inhibitor rapamycin could block IAV replication in vitro [ 69 , 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…MAPK and autophagy signaling pathways contributed to IAV virus-induced inflammation and lung injury [ 65 , 66 ]. FOXO signaling pathway has also been showed playing an important role in the IAV-induced alveolar macrophage dysfunction [ 67 ], and FoxO1 negatively regulated cellular antiviral response by promoting degradation of IRF3 [ 68 ]. The mTOR signaling pathway was most important for early IAV replication, and the use of mTOR inhibitor rapamycin could block IAV replication in vitro [ 69 , 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are currently no human studies available evaluating the effectiveness of higher dietary polyphenol, lignan and phytosterol intake in reducing COVID-19 risk. However, the antiviral efficacy of polyphenols including lignans and plant sterols has been confirmed against SARS-CoV, MERS-CoV, Ebola virus, HIV, influenza virus and other viruses causing respiratory tract infections (18)(19)(20)(21). Recent studies have also demonstrated their beneficial effects against the SARS-CoV-2 virus (18,(22)(23)(24) resulting from their ability to bind to peak protein sites on the ACE2 receptor used by SARS-CoV-2 to infect cells (25, 26), regulate ACE2 expression and also interfere with SARS-CoV-2 replication by inhibiting the virus protease or inhibiting SARS-CoV-2 RNA-dependent RNA polymerase (RdRp) (27,28).…”
Section: Discussionmentioning
confidence: 99%
“…M . scabra flavonoids (MSF), in which the major active compounds were luteolin, apigenin, kaempferol, and moslosooflavone, decreased protein expressions of phosphating Akt/FoxO1 in both the lung tissues of IAV-infected mice as well as IAV-infected macrophages [ 122 ]. FoxO3a played an important role in glucocorticoids treatment of SLE by suppressing pro-inflammatory response.…”
Section: Function Of the Foxo Transcription Factors In Immune Cellsmentioning
confidence: 99%